Anno genominis XX: 20 years of Arabidopsis genomics. Issue 4 (29th December 2020) - Provart, Nicholas J; Brady, Siobhan M; Parry, Geraint; Schmitz, Robert J; Queitsch, Christine; Bonetta, Dario; Waese, Jamie; Schneeberger, Korbinian; Loraine, Ann E
Abstract: Twenty years ago, the Arabidopsis thaliana genome sequence was published. This was an important moment as it was the first sequenced plant genome and explicitly brought plant science into the genomics era. At the time, this was not only an outstanding technological achievement, but it was characterized by a superb global collaboration. The Arabidopsis genome was the seed for plant genomic research. Here, we review the development of numerous resources based on the genome that have enabled discoveries across plant species, which has enhanced our understanding of how plants function and interact with their environments. Abstract : The publication of the Arabidopsis genome sequence 20 years ago has had an enormous impact on the global plant science community.